IMPLEMENTASI ROUTING OPEN SHORTEST PATH FIRST (OSPF) MELALUI TUNNEL OPEN VPN - Tri Mulyadin; Muhammad Sholeh; Catur Iswahyudi (Jurnal Jarkom, 2016)
To connect the office with another office in different location, it takes the transmission media for data communication. one of the transmission media that can be used is Open VPN using the internet. OSPF routing required to connect all routers in the network using a VPN.OSPF routing on the Open VPN network, could be a solution for companies who want to build a network to connect multiple offices in different locations with a network.The implementation of OSPF routing in the Open VPN network uses three pieces of routerboard with one public IP. The testing is done by analyzing the process of selection of routing line, analysis of time speed of convergence, analysis of speed is the literature study, simulation to the virtualbox, and implementation to test-bed network.The test results convergence time using the same ISP is55,28 seconds and using a different ISP is 55,seconds. Test results on the routing update process with the same ISP is 7,23 and 9,63 seconds using a different ISP. Overall the OSPF routing on the Open VPN networks able to work well with convergence time and time routing updates fast and up to date